Discourse Markers as Cues for Topic Shift Interpretation: Experimental Evidence from Spanish - Mercedes Villalobos Cardozo; Ludivine Crible; Liesbeth Degand (Discours)
Despite the complex terminological panorama regarding discourse markers (hereafter DMs) and the elusiveness of the notion of discourse topic, the relationship between these linguistic phenomena is a long-standing one. Descriptions linking the two are present in early work on DMs and are still the subject of ongoing discussion. Often, however, these characterisations, which present certain DMs as cues for topic management in interaction, are made from a corpus-based perspective. Here, as part of a larger mixed-methods project investigating DMs from production to prediction, we explore participants’ interpretations of discourse topic in conversation when introduced by three DM configurations in Spanish: y (“and”), perceived lengthened y (“and”), and the combination bueno y (“well and”). This is achieved through an experimental forced-choice task and the qualitative analysis of the material presented, based on authentic data in Spanish. By doing so, we examine the intricate relationship between DMs and their context to disentangle their actual contribution to the interpretation of discourse topic. Results show that these DMs do not override the semantic content of the utterances and, therefore, only moderately contribute to recognising topic continuity or topic discontinuity. An analysis of the content of the utterances presented in our stimuli allowed us to create a set of strong and weak strategies for topic (dis)continuity that seem to help speakers with the topic interpretation task.